Public administration, the history of ideas, and the reinventing government movement - Spicer, Michael (2004)
Public administration writers, with some notable exceptions, generally have not paid a great deal of attention to the history of ideas. However, public administration inquiry is profoundly affected by longstanding political and social ideas. This article shows how the idea of the state as a purposive association - that is to say, a collective enterprise that is driven by some set of substantive ends or purposes - has helped to shape the thinking and discourse of some public administration writers, particularly those of the reinventing government movement. The implications of this for public administration inquiry and education are examined. - Reproduced.
Keywords: Public administration